Interfacial memristors in Al–LaNiO3 heterostructures. Issue 26 (21st June 2017) - Tian, Bobo; Nukala, Pavan; Hassine, Mohamed Ben; Zhao, Xiaolin; Wang, Xudong; Shen, Hong; Wang, Jianlu; Sun, Shuo; Lin, Tie; Sun, Jinglan; Ge, Jun; Huang, Rong; et al.
Abstract : Self-assembled interfacial memristive systems in Al–LaNiO3 heterostructures. Abstract : Memristive devices are promising circuit elements that enable novel computational approaches which go beyond the von-Neumann paradigms. Here by tuning the chemistry at the Al–LaNiO3 (LNO) interface, a metal–metal junction, we engineer good switching behavior with good electroresistance (ON–OFF resistance ratios of 100), and repeatable multiple resistance states. The active material responsible for such a behavior is a self-formed sandwich of an Al x O y layer at the interface obtained by grabbing oxygen by Al from LNO. Using aberration corrected electron microscopy and transport measurements, it is confirmed that the memristive hysteresis occurs due to the electric field driven O 2− (or ) cycling between LNO (reservoir) and the interlayer, which drives the redox reactions forming and dissolving Al nanoclusters in the Al x O y matrix. This work provides clear insights into and details on precise oxygen control at such interfaces and can be useful for newer opportunities in oxitronics.